No interaction between out-degree term and other network generating parameters. - Matthew Aguirre (9558032) (2025)
Counts of the number of genes which are strong knockouts (KOs, top row) and key target genes (bottom row) in each synthetic GRN. Each panel shows all 1,920 GRNs as individual points, across values of network generating parameters (x-axes), with additional stratification by the out-degree term . Each distribution is annotated with its mean over GRNs in each bin (diamond points). There is no obvious visual evidence for interactions between the parameters. (TIFF)